PARADIGMA PENAFSIRAN ALQURAN NUSANTARA (Analisis Tafsir Aceh â€˜Tafsir Paseâ€™) - Talebe, Tamrin (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: This article discussesÂ TafsÄ«r Pase, a local exegesis of the Qur'an. The tafsÄ«r was written in Aceh in pre independence day, brought about by the unstable social conditions (conflict). These conditions have implications on the pattern of this tafsÄ«r, so that the contains cover the ideas on the empowerment ofÂ Acehnese, expected to increase the unity and the brotherhood among them. TafsÄ«r Pase compiled by a team of five people. The name â€œPaseâ€, which is used as the name of this tafsÄ«r, was Â taken from one of the oldest kingdoms in Aceh. It is interesting that this quranic exegesis begins with the study of 'UlÅ«m al-Qur'Än before entering the discussion of tafsÄ«r using cultural approach.Kata Kunci: Tafsir Pase, Aceh, pendekatan kebahasaan, sastra lokal